Are there bubbles in sectoral indices? Evidence from national stock exchange - Suresh G.; Naveen Kumara R.; Natchimuthu Natchimuthu (Cogent Economics & Finance, 2022)
Trading at prices above their fundamental values has been referred to as stock market Bubbles. These Bubbles, when Busted, can lead to a market Crash. From experience, it is a well-known fact that Bubbles initially occur in one particular sector and later spread to the aggregate markets, leading to the collapse of the entire market. This paper attempts to test the existence of bubbles in Indian Sectoral Indices. Previous studies have proven that sectoral indices do not mimic the market behaviour and the reaction of the sectors tends to be different compared to the market's response. In that context, the paper aims to explore the existence of bubbles sector-wise rather than aggregate market-wise. The presence of bubbles is confirmed through the Superior and flawless method called the GSADF test is more flexible and reliable than RADF (Rolling Augmented Dickey-Fuller) and Supremum Augmented Dickey-Fuller (SADF) methods. Findings reveal that not all sectors experience bubbles at the same time. During the study period, the Automobile, financial services, Media and Private sector banking sectors experienced bubbles. Detected bubbles were also found at different times in these sectors. The study helps investors who focus investments in a specific sector to capitalise on price movements once they can time-stamp the occurrence of bubbles. The study provides essential input for investors in taking timely investment decisions. Further results of our study could enable policymakers to instil corrective actions to put the markets back on track when the index falsely deviates from intrinsic values.
Keywords: 330; bubble; GSADF; sectoral indices; stock market